Reflecting customers’ innovativeness and intention to adopt islamic banking in Nigeria / Ahmad Muhammad Gumel and Mohammad Azmi Othman - Othman, Mohammad Azmi (Faculty of Business Management, 2013)
The primary objectives of this study are to investigate the relationship between consumer innovativeness and customers’ intention to adopt Islamic banking (2) to investigate the role of consumer innovativeness in relationship between attitudes, social influence, perceived behavioural control and intention to adopt Islamic banking in Nigeria.The methodology that will be adopted in order to achieve the stated objectives of the research will therefore be a positivist methodology namely: the development of hypothesis to address research questions; use of questionnaire to obtain quantitative data from a reliable sample; and statistical analysis to test the hypothesis.This proposed research framework would compliment efforts of previous researchers by investigating the factors influencing customer’s intention to adopt Islamic banking in Nigeria. It focuses on the relationship between consumer innovativeness, attitude, social influence, perceived behavioral control and intention to adopt the new mode of financing.In addition, it is expected that the relative influence of these independent variables will vary when consumer innovativeness was set to moderate the relationship.